Development and Validation of a Nomogram Based on Motoric Cognitive Risk Syndrome for Cognitive Impairment - Liu, Yong; Wei, Kai; Cao, Xinyi; Jiang, Lijuan; Gu, Nannan; Feng, Lei; Li, Chunbo (Frontiers in Aging Neuroscience, 2021)
Objective: To develop and validate a prediction nomogram based on motoric cognitive risk syndrome for cognitive impairment in healthy older adults. Methods: Using two longitudinal cohorts of participants (aged ≥ 60 years) with 4-year follow-up, we developed (n=1,177) and validated (n=2,076) a prediction nomogram. Lasso regression model and multivariable Cox regression analysis was used for variable selection and to develop the prediction model, respectively. The performance of the nomogram was assessed with respect to its calibration, discrimination, and clinical usefulness. Results: The individualized prediction nomogram was assessed based on the following: motoric cognitive risk syndrome, education, gender, baseline cognition, and age. The model showed good discrimination (C-index of 0.814 [95% Confidence Interval, 0.782 to 0.835]), and good calibration. Comparable results were also seen in the validation cohort which includes good discrimination (C-index, 0.772 [95% Confidence Interval, 0.776 to 0.818]), and good calibration. Decision curve analysis demonstrated that the prediction nomogram was clinically useful. Conclusions: This prediction nomogram provides a practical tool with all necessary predictors which are accessible to practitioners. It can be used to estimate the risk of cognitive impairment in healthy older adults.